PENINGKATAN AKTIVITAS DAN HASIL BELAJAR IPA MELALUI METODE KOOPERATIF TIPE JIGSAWPADA SISWA KELAS VIII-1 SMP NEGERI 3 TEBING TINGGI - Mangatur Silitonga (PGSD Universitas Negeri Medan, 2018)
This aim of this research is to improve learning result on science subject through cooperativejigsaw method of jigsaw type. This classroom action researchconducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class VIII-1 SMP Negeri 3 Tebing Tinggi which amounted to 37 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the cooperative methodof jigsaw type inscience subjects can improve student learning result characterized by increased mastery learning students, namely the first cycle (72,97%) , cycle II (89,18 %) and complete learn the clasical equal to 89,18%.Key words: Jigsaw, cooperative, science